1973
DOI: 10.1038/bjc.1973.157
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Electron Spin Resonance Spectra of Whole Blood from Normal and Tumour Bearing Patients

Abstract: Summary.-Electron spin resonance spectra have been obtained from samples of frozen whole blood or separated blood cells and plasma. Blood samples were obtained from human controls having no diagnosed malignancy and from patients with a variety of benign and malignant tumours.The characteristic spectrum from control blood shows two main lines with g values of 4-2 and 2-049. Several smaller lines can also be observed. The line at g = 2-049 may be due to the copper protein ceruloplasmin. Although no qualitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…Cp increases sharply in the sera of cancer bearing hosts (12). We found the elevated ESR signal of cupric ions in sera of DAB hepatoma-bearing rats, as had been recognized in various cancer patients (11) . Although the scavenging activity of Cp against superoxide anion radicals is substantially less than that of erythrocyte superoxide dismutase (21), it may still play a significant role as circulating scavenger of oxygen-derived free radicals.…”
Section: Resultssupporting
confidence: 69%
“…Cp increases sharply in the sera of cancer bearing hosts (12). We found the elevated ESR signal of cupric ions in sera of DAB hepatoma-bearing rats, as had been recognized in various cancer patients (11) . Although the scavenging activity of Cp against superoxide anion radicals is substantially less than that of erythrocyte superoxide dismutase (21), it may still play a significant role as circulating scavenger of oxygen-derived free radicals.…”
Section: Resultssupporting
confidence: 69%
“…Most studies in the past have been made using a general batch of patients who were unsorted as regards the type of treatment they were receiving. This is true of the preliminary report of this team (Foster et al, 1973) where elevations in caeruloplasmin signal were found in patients with breast cancer when considered as an unsorted group. The present study shows that, if only those patients who are not receiving treatment are considered, this elevation, although still present, is very small.…”
Section: Normal Subjectsmentioning
confidence: 82%
“…A study of electron spin resonanace (ESR) signals from caeruloplasmin by Swartz and Wiesner (I1972) showed an increase in signal size in mixed cancer patients, and a decrease on response to radiotherapy. Foster et al (1973) showed that caeruloplasmin (g 2.049) and Fe transferrin (g , 4.2) levels can be measured by ESR in whole, frozen blood and that a small increase in mean size of caeruloplasmin signal can be detected in patients suffering from malignant diseases as compared with healthy controls. A larger-scale investigation of malignant lymphoma (Foster et al,1 977a,b) has shown that the already-known variations in serum Cu with disease activity in Hodgkin's disease can be detected by ESR and that these are much less marked in non-Hodgkin's lymphoma.…”
mentioning
confidence: 99%
“…Recently e.s.r. has been used to demonstrate similar increases in the blood of patients with Hodgkin's disease and with cancers of the breast (Foster et al, 1973) and to study the effects of radiotherapy on plasma ceruloplasmin concentrations in a variety of cancer patients (Swartz and Wiesner, 1972). However, serum ceruloplasmin concentrations also increase during pregnancy, acute and chronic infections, collagen disorders and myocardial infarction, following surgery and after administration of oestrogens and thyroid and pituitary hormones (Hrgovcic et al, 1973c;Hughes, 1972;Owen, 1967).…”
Section: Spleenmentioning
confidence: 99%